PENGGUNAAN MEDIA PAPAN MAGNETIK UNTUK MENINGKATKAN PEMAHAMAN MATERI ARAH MATA ANGIN PADA DENAH MATA PELAJARAN IPS SISWA KELAS III MINU WEDORO - Lestari, Farida Dian (Journal Of Islamic Elementary School (JIES), 2021)
This research is motivated by the difficulty of students of class III-C to understand the direction of the wind material on the IPS subject plan. The formulation of the problem in this study are: (1) How is the application of magnetic board learning media in improving understanding of wind direction material on social studies lesson plans of class III students of MINU Wedoro. (2) How to increase the understanding of wind direction material on social studies lesson plans for class III students of MINU Wedoro. This research is a Classroom Action Research with Kurt Lewin's model, which consists of 4 stages, namely planning, implementation, observation or observation, and reflection, which are carried out in 2 (two) cycles. Data analysis techniques used are qualitative and quantitative data, by collecting data using tests, observations, interviews, and documentation. The subjects of this study were MINU Wedoro class III-C students in the 2017-2018 school year, totaling 30 students. The results of this study indicate that: 1) The use of magnetic board media in improving students' understanding regarding the material in the direction of the wind on a floor plan of social studies can be well implemented. This can be proven through the observation of teacher activities in the first cycle which scores 72 (enough) and increases in the second cycle by 93 (Very good), while the activities of students in the first cycle get a score of 70 (enough) and increase in the cycle II for 94 (Very Good). 2) Increased understanding of wind direction material on class III Social Sciences lesson plans after the application of magnetic board media can be seen in the results of the average score of students, at the pre cycle of 70.5 (Enough) with a percentage of completeness of 33% (Less) , to be 78 (Good) in the first cycle with a percentage of completeness of 73% (Enough), and increase in the second cycle of 85 (Very Good) with a percentage of completeness of 93% (Very Good).